Communism, Culture, and Financial Development - Klein, Alina F.; Klein, Rudolf F. (International Journal of Economics and Financial Issues, 2017)
This paper analyzes the relationship between culture and financial development in Europe, with culture defined as informal constraints on human interactions. We assert that various national characteristics such as people's trust and trustworthiness, and the level of control they feel they have over their lives can modify transaction costs, which in turn leads to different levels of financial development. Furthermore, we consider communism as an exogenous shock to the cultural values existent in Central and Eastern Europe. This exogenous component of culture is negatively related to present financial development, even after controlling for other historical variables such as religion and formal institutions at the beginning of the 20th century. Via 2SLS regression analysis, we show that communism has shaped cultural values, which in turn affect financial development. Keywords: Financial development; Culture; Transition economies; Communism; Economic growth. JEL Classifications: F43; F63; F65; P20; Z10.